2021
DOI: 10.3389/fphar.2020.601751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Panax notoginseng Saponins and Major Anti-Obesity Components on Weight Loss

Abstract: The prevalence of individuals who are overweight or obese is rising rapidly globally. Currently, majority of drugs used to treat obesity are ineffective or are accompanied by obvious side effects; hence, the options are very limited. Therefore, it is necessary to find more effective and safer anti-obesity drugs. It has been proven in vivo and in vitro that the active ingredient notoginsenosides isolated from traditional Chinese medicine Panax notoginseng (Burk.) F. H. Chen exhibits anti-obesity effects. Notogi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 128 publications
0
20
0
Order By: Relevance
“…Panax notoginseng (Burkill) F.H. Chen could change the fat and inflammation of liver tissue through decreasing expression levels of SREBP1c, ACC, and FAS ( Ji and Gong, 2007 ; Yan-Xia et al, 2011 ; Zhang et al, 2020 ). The expression levels of SREBP1c, ACC, and FAS were downregulated in the Curcuma longa L. groups compared to the HFD groups ( Ejaz et al, 2009 ; Ahn et al, 2010 ; Zhao et al, 2011 ; Mun et al, 2019 ).…”
Section: Targeting Lipid Metabolism With Bioactive Compounds From Tcms With Anti-obesity Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Panax notoginseng (Burkill) F.H. Chen could change the fat and inflammation of liver tissue through decreasing expression levels of SREBP1c, ACC, and FAS ( Ji and Gong, 2007 ; Yan-Xia et al, 2011 ; Zhang et al, 2020 ). The expression levels of SREBP1c, ACC, and FAS were downregulated in the Curcuma longa L. groups compared to the HFD groups ( Ejaz et al, 2009 ; Ahn et al, 2010 ; Zhao et al, 2011 ; Mun et al, 2019 ).…”
Section: Targeting Lipid Metabolism With Bioactive Compounds From Tcms With Anti-obesity Effectsmentioning
confidence: 99%
“…Compared with the modern drugs mentioned above, TCMs have been widely used to treat obesity for a very long time. This fact alone suggests that TCMs may be used as a vast resource for the development of natural anti-obesity drugs possessing fewer side effects ( Li et al, 2017 ; Martel et al, 2017 ; Zhang Y. et al, 2018 ; Zhang et al, 2020 ; Ji-Ping et al, 2021 ). While some of the anti-obesity effects and mechanisms of TCMs have been studied in the past decade, most of these studies only focused on single/several genes or signaling pathways involved in lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…P. notoginseng saponins (PNS) and ginsenosides Rb2 and Rd2 inhibit platelet activity [ 2 – 4 ]. PNS exhibit antiobesity [ 5 ] and antidiabetic properties [ 6 ] and also attenuate nonalcoholic fatty liver disease [ 7 ]. Of note, P. notoginseng is found to be cardio-protective as PNS protect against acute myocardial infarction in mice [ 8 ] and relieve the focal cerebral ischemia-reperfusion in rats [ 9 ], while notoginsenoside R1 promotes angiogenic activity in endothelial cells and zebrafish [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 Additionally, Zhang et al reported that P. notoginseng exerts anti-obesity effects by downregulating lipid synthesis, inhibiting adipogenesis, and upregulating energy consumption. 11 Yang et al demonstrated that P. notoginseng can attenuate lung cancer growth partly by modulating the Met/miR-222 axis. 12 Hu et al reported that P. notoginseng attenuates the lipopolysaccharide-induced blood-brain barrier disruption and monocyte adhesion to cerebral endothelial cells in vitro by activating the Nrf2 antioxidant defense system through a PI3K/Akt-dependent mechanism and inhibiting the NF-κB inflammatory signaling pathway.…”
Section: Introductionmentioning
confidence: 99%